The Palgrave Handbook of Presidents and Prime Ministers From Cleveland and Salisbury to Trump and Johnson - Cullinane, Michael Patrick; Farr, Martin (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XIV, 495 p. 10 illus. in color.